The Southern Indian Ocean and the Oceanic South. Issue 1 (1st June 2022) - Lavery, Charne
Abstract : The southern Indian Ocean constitutes a distinct oceanographic region that offers useful links, connections, and perspectives as an area of inquiry, in the domain of colonial and postcolonial literature but also more widely. The region is both particularly oceanic and particularly southern, making it a key part of the 'oceanic South', a formulation which overlays the postcolonial poverty of the Global South with its oceanicity. As an area of inquiry it complicates Indian Ocean studies by drawing its purview into colder, wilder, more oceanic regions; centralizes questions of the global – and oceanic – South; and encourages a focus on the ocean itself. The article describes the material characteristics of the southern Indian Ocean, places it within the oceanic South, and as an example reads a work of historical fiction – Dan Sleigh's Islands (2005) – within this particular oceanic, political, and literary geography.